2004
DOI: 10.1007/s10534-004-1226-8
|View full text |Cite
|
Sign up to set email alerts
|

Testicular toxicity induced by dietary cadmium is associated with decreased testicular zinc and increased hepatic and renal metallothionein and zinc in the bank vole (Clethrionomys glareolus)

Abstract: Mechanism of testicular toxicity induced by dietary cadmium (Cd) has been less investigated than that following acute Cd injection. In the present study we characterized testicular injury in a small rodent, the bank vole, exposed subchronically to dietary Cd in a quantity of 0.9 micromol/g, and determined the importance of some factors (Cd accumulation, metallothionein (MT), oxidative stress, and zinc (Zn)) in the injury. Dietary Cd induced moderate histopathological changes (hemorrhage in interstitium, necros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 52 publications
6
25
0
Order By: Relevance
“…The levels of these two metals become in line with controls after the administration of antioxidants such as vitamin E, sulforaphane, and Ficus religiosa plant extract. These results concomitant with earlier studies [Bonda et al 2004;Yiin et al 1999] show that Cd could also be one of the reasons for causing reduction of Zn, thus leading to increased oxidative stress in the testicular tissues of rats. Essential elements, such as Zn and Se are powerful antioxidants that are important for the regulation of male reproduction.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The levels of these two metals become in line with controls after the administration of antioxidants such as vitamin E, sulforaphane, and Ficus religiosa plant extract. These results concomitant with earlier studies [Bonda et al 2004;Yiin et al 1999] show that Cd could also be one of the reasons for causing reduction of Zn, thus leading to increased oxidative stress in the testicular tissues of rats. Essential elements, such as Zn and Se are powerful antioxidants that are important for the regulation of male reproduction.…”
Section: Discussionsupporting
confidence: 89%
“…Zinc depletion may also be due to its obstruction through Cd caused by liver metallothioneins from the blood plasma, thus raising its level in the liver cells and maybe sequestering the supply of Zn to many other tissues e.g. testes [Bonda et al 2004]. Faure et al [2007] have reported that together vitamin E plus Zn are much more effective than Zn alone to enhance the antioxidant mechanism of defense in many animal models of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In the same vein, Amer et al (22) demonstrated the antioxidant characteristics of zinc in old rats. It was also reported in previous studies that zinc metallothionein offered a signifi cant degree of protection in the kidney (10) and testis (9). In addition to its direct antioxidant characteristics, zinc may have brought about these effects through its effect on thyroid function, and therefore on thyroid hormone levels.…”
Section: Tab 1 Mda (Nmol/ml) and Gsh (Mg/dl) Levels Of Study Groupsmentioning
confidence: 71%
“…It has been reported in several research studies examining the antioxidant effects of zinc that it inhibits the damage induced by various procedures in the testis and kidney tissues (9,10).…”
mentioning
confidence: 99%
“…Thus toxicity of Cd may result from disturbances in Zn metabolism, leading to the description of Cd as an antimetabolite of Zn. The most compelling reason for the protective effects of Zn against Cd toxicity is that Zn induces the protection of the metal binding protein metallothionein (MT) (Salem et al, 2008, Bonda et al, 2004. Hence, this may be the cause for lowering the concentration of Cd in the select tissues primarily in 30d kidney (8.327±0.450 µg/g).…”
Section: Resultsmentioning
confidence: 99%